Respect to Professional Secrecy Over Public Interest in Forensic Medical Practice - Gunathilake, K.M.T.B.; Vidanapathirana, M. (Medico-Legal Society of Sri Lanka, 2015)
Introduction Respecting the patients' autonomy and privacy is one of the main objectives in medical practice. Forensic pathologists are doctors those who are bound to protect and respect the patient's and the victim's autonomy and rights. Objectives To introduce a guidance to handle the ethico-Iegal issues by using case scenarios, in cases where there is intense fear among residents and high public and media interest. Case 1: There was public unrest and social phobia in Sri Lanka due to the attacks of the "Grease Yaka". On examination, the injuries were either self-inflicted or not compatible with-the history. Case 2: In Sabaragamuwa area, many old and middle aged females were killed. According to two postmortem investigations that were conducted in 2014 and 2015, they were related to personal or family problems. Case 3: A student from Jaffna was found hands tied inside a bathroom in one of higher education institutes in Sabaragamuwa. On examination, injuries were self-inflicted or caused by friendly hand. Information that facilitate criminal investigations were divulged in good faith and in case 1 and 2 to alleviate the public fear, and in case 3 to avoid public unrest among ethnic groups. Conclusion Divulgence of information should be limited to the relevant recipient and used for investigations. The personal information must be kept secret until the full report is submitted to ~he courts. Doctors have absolute privilege to produce a complete report to the courts. Still some information could be retained without expressing within the court house and the doctor can seek permission of the judge to divulge in writing. Respect professional secrecy of data without divulging unless if there-is special relevance, and even in such instances that should be done in good faith.
Keywords: Ethico-legal issues; Grease Yaka; Public unrest